Ginsenoside Rg1 alleviates lipopolysaccharide-induced pyroptosis in human periodontal ligament cells via inhibiting Drp1-mediated mitochondrial fission. (March 2023) - Chu, Kefei; Zhang, Zhenghao; Chu, Yi; Xu, Yao; Yang, Wanrong; Guo, Ling
Abstract: Objective: The present study aimed to investigate whether Ginsenoside Rg1 alleviated lipopolysaccharide (LPS) ‐ induced pyroptosis of human periodontal ligament cells (HPDLCs) and further explore the underlying mechanism. Design: Cell viability was detected using the CCK-8 assay. Proinflammatory cytokine secretion and lactate dehydrogenase release were examined by ELISA. Flow cytometry analysis was conducted to determine the pyroptosis ratio, and ATP production was estimated using the ATP assay kit. Fluorescence staining was utilized to visualize mitochondrial morphology and analyze mitochondrial reactive oxygen species (mtROS), and the mitochondrial membrane potential level. Western blot and qRT-PCR were used to determine the expression of signaling pathway-related proteins and mRNA, respectively. Results: The results discovered that Ginsenoside Rg1 treatment enhanced cell viability in comparison to LPS stimulation, attenuated pyroptosis in HPDLCs, and reduced the release of lactate dehydrogenase, IL-1β, and IL-18 significantly. Additionally, we found that Ginsenoside Rg1 upregulated ATP content and mitochondrial membrane potential level while reducing aberrant mitochondrial fission and mtROS production. Mechanistically, we found that Ginsenoside Rg1 upregulated dynamin-related protein 1 (Drp1) phosphorylation at Ser 637 in an AMP-activated protein kinase (AMPK)-dependent manner, and reduced pyroptosis-related proteins expression, including NLRP3, ASC, Caspase-1, and GSDMD-NT. Conclusions: These findings demonstrate that Ginsenoside Rg1 treatment attenuates LPS-induced pyroptosis and inflammation damage in HPDLCs, which may connect to the activation of the AMPK/Drp1/NLRP3 signaling pathway. Moreover, the results offer a potential theoretical foundation for applying Ginsenoside Rg1 in inflammatory diseases such as periodontitis. Graphical Abstract: ga1 Highlights: Lipopolysaccharide (LPS) triggers NLRP3-mediated pyroptosis. LPS induces Dynamin-related protein 1 (Drp1)-mediated mitochondrial fission. Ginsenoside Rg1 suppressed mitochondria fission by activating AMPK signaling. Ginsenoside Rg1 alleviated pyroptosis via regulating AMPK/Drp1/NLRP3 pathway.